Human impact on the environment : ancient roots, current challenges - Judith , E. Jacobsen (ed.) (San Francisco, 1992)
This book explores ways in which human culture and technology have altered the environment over the long sweep of history. The contributors, drawn from a wide variety of disciplines including anthropology, biology, history, economics, physies, and atmo spheric science, find that adverse human impact on the environ ment extends back to early human history and is not solely an artifact of the onset of the Industrial Revolution. Indeed, the analysis in this book shows that throughout human history short-term strategies for coping with immediate problems have led to long-term negative consequences, most of them unforeseen.
Keywords: Human ecology